Chlorella spp. as an emerging source for anticancer remedy and nutraceuticals: an sdvance study - Ferdous, Umme Tamanna; Khan, Shakeel Ahmad; Shakoor, Adnan; Uddin, Shihab; Nazarudin, Muhammad Farhan; Zia, Abdul Wasy (Taylor and Francis, 2025)
Microalgae are becoming popular to exploit in industrial usage because of their diversified array of phytochemicals, prompt growth rate, ability to grow in season or extreme ambience, and the fact that they do not require arable land and fresh water. They are an excellent reservoir of precious and pharmaceutically important phytochemicals, like carotenoids, polyphenols, lipids, phycobiliproteins, and vitamins. These compounds have shown in vitro and in vivo anticancer activities towards various cancer cells. Consequently, because of its excellent anticancer, antioxidant, and anti-inflammatory properties, Chlorella spp. are also getting attention in pharmaceutical and nutraceutical companies, which this review discusses. Along with their cytotoxicity mechanism, other major bioactivities, especially antioxidant and immunomodulatory effects with possible mechanisms, have also been discussed. Recent advances in elucidating various Chlorella species’ anticancer potential have also been documented. Moreover, a bibliometric analysis has been performed to evaluate the current trend in Chlorella anticancer research. The information provided in this review will effectively identify cutting-edge research trends on Chlorella and maximize the potential of new technology for pharmaceutical and nutraceutical industries.